Judy Moody, Girl Detective - McDonald, Megan; Reynolds, Peter, 1961- (Somerville, Mass. : Candlewick Press, 2010)
When a puppy who is being trained as a police dog goes missing, third-grader Judy forms a detective agency to solve the mystery, imitating her literary heroine, Nancy Drew.
"No. 9"--Spine.
Keywords: Lost and found possessions -- Fiction; Police dogs -- Fiction; Labrador retrievers -- Fiction; Dogs -- Fiction; Drew, Nancy (Fictitious character) -- Fiction; Siblings -- Fiction; Fiction